2003
DOI: 10.1180/0026461036760154
|View full text |Cite
|
Sign up to set email alerts
|

Fungal involvement in bioweathering and biotransformation of rocks and minerals

Abstract: In the Earth’s lithosphere, fungi are of fundamental importance as decomposer organisms, animal and plant pathogens and symbionts (e.g. lichens and mycorrhizas), being ubiquitous in sub-aerial and subsoil environments. The ability of fungi to interact with minerals, metals, metalloids and organic compounds through biomechanical and biochemical processes, makes them ideally suited as biological weathering agents of rock and building stone. They also play a fundamental role in biogeochemical cycling of nutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
244
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(249 citation statements)
references
References 196 publications
(228 reference statements)
4
244
0
1
Order By: Relevance
“…Numerous studies on microbe-mineral interactions have shown that micro-organisms substantially affect the process of mineral weathering (termed "bioweathering" hereafter) (Burford et al, 2003;Gadd, 2007;Hoffland et al, 2004;Hutchens et al, 2003;Kalinowski et al, 2000). Despite this increasing evidence that microbial cells can play a major role in mineral alteration, the processes occurring at the cell-mineral interface remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on microbe-mineral interactions have shown that micro-organisms substantially affect the process of mineral weathering (termed "bioweathering" hereafter) (Burford et al, 2003;Gadd, 2007;Hoffland et al, 2004;Hutchens et al, 2003;Kalinowski et al, 2000). Despite this increasing evidence that microbial cells can play a major role in mineral alteration, the processes occurring at the cell-mineral interface remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the roles of fungi in geologically relevant processes, such as metal and mineral transformations, can be termed geomycology, an important part of the more general area of geomicrobiology (Gadd 2007, 2010). In the terrestrial environment, such processes are important in rock bioweathering, contributing to the formation and development of mineral soil, and global biogeochemical cycles for component elements, including their availability to living organisms (Sterflinger 2000; Burford et al 2003; Gadd 2007). In aerobic terrestrial environments, free-living and symbiotic fungi are of great importance, especially when considering rock surfaces, soil and the plant root–soil interface.…”
Section: Characteristics Of Rock Transforming Fungimentioning
confidence: 99%
“…Fossilised fungal structures have been reported from a variety of mineral substrates including Devonian Rhynie Chert, as fossil lichen mycobionts in stromatolites, in Djebel-Onk phosphorites, Triassic silicified rock, Bitterfield amber and Tertiary Dominican amber (see Burford et al 2003). Various types of endoliths, including fungi, have been found in marine shells in the Late Ordovician and Middle Devonian volcanic rocks, while microborings have also been found in early Cambrian phosphatic and phosphatised fossils (Taylor et al 2015).…”
Section: Natural Historymentioning
confidence: 99%
See 2 more Smart Citations